Complex investigations on the river Vardar. II. The most polluted sites in the first three months - Krstić, Svetislav; Melovski, Ljupčo; Levkov, Zlatko; Stojanovski, Panče (Macedonian Journal of Ecology and Environment, 1994)
Presented article refers to complex physic-chemical and floristic investigations on river Vardar, Macedonia. The study has been started in February 1993 and the most polluted sampling sites along the river flow, amid the first one in high mountain region, in the first three months are presented. In addition to 25 controlled physic-chemical parameters diatom flora communities were investigated through app. 1600 permanent slides. Diatom flora composition and floristic statistical indices in relation to determined pollution are discussed.